Resisting Behavior of Modern Western Education in Awad Punch - Irsa Kokab; Dr. Humaira Ishfaq (دریافت)
Creating literature is in itself a resistance process. Resistance literature is anti-oppression and anti-exploitation literature. The period in which Urdu literature began is a period of political, social and cultural decline. This decline began at the beginning of the eighteenth century. The year 1857 is a focal point in the history of political decline, and the prose of Awad Panch is a mirror of the injustice, oppression, violence, and barbarism that took place after 1857. The most widely discussed and criticized subject of Awad Punch magazine in its more or less forty years of life was Western education and culture and probably the activities of Sir Syed movement and its comrades in this regard. Be the target. An important and significant achievement of the Awad Punch is its resistance against this colonial society.